Two new Rhitymna species (Araneae: Sparassidae) from Hainan Island, China - Quan, Dan; Liu, Jie (Zootaxa, 2012)
Two new species of the genus Rhitymna are described from Hainan Island (southern China): Rhitymna tangi sp. nov., Rhi-tymna macilenta sp. nov. Morphological descriptions and illustrations of the two new species are given. The type speci-mens of those new species are deposited in the Institute of Zoology, Chinese Academy of Sciences in Beijing (IZCAS) and in college of Life Sciences, Hubei University in Wuhan (HBU).